Perlindungan Hukum bagi Anak Luar Nikah di Indonesia; Studi Komparasi Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 dan Hukum Islam - Hutasoit, Eunike Loist; Siagian, Fedro Julio Carlos; Zulkifli, Suhaila; Noor, Tajuddin (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, legal protection for children born out of wedlock should ensure that they receive civil rights equivalent to those of legitimate children without discrimination. In reality, there are still differences in treatment between positive law in Indonesia, especially after the Constitutional Court Decision No. 46/PUU-VIII/2010, and Islamic law, which holds differing views on the status of children born out of wedlock. The challenge lies in how to harmonize legal protection for these children amidst the differing perspectives between positive law and Islamic law, ensuring that their civil rights are upheld while also minimizing negative social impacts, such as fornication. The purpose of this study is to analyze and compare legal protection for children born out of wedlock according to the Constitutional Court Decision and Islamic law and to seek solutions that can integrate both perspectives to create fair and dignified legal protection. The methodology used in this study is a normative juridical approach, examining various laws, court decisions, and related Islamic legal literature. The results of the research indicate that although there are differences in views between the Constitutional Court's decision and Islamic law, the integration of both approaches can provide more comprehensive legal protection for children born out of wedlock. By balancing both perspectives, it is hoped that it will guarantee the civil rights of these children while also preserving societal morality by minimizing the practice of fornication.